Telenovelas in Brazil: From Traveling Scripts to a Genre and Proto-Format both National and Transnational - Straubhaar, Joseph (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, we argue that there are several layers of genre, proto-format commercialization of program elements, and current commercially licensed formats. Some genre traditions, like melodrama, tend to be large, over-arching categories that already have a long history before television (Martín-Barbero 1993). Speciﬁc genres of television production, like the U.S. soap opera or the Latin American telenovela can develop within that larger tradition. Even more speciﬁc genres, like the Brazilian socially engaged or historical telenovelas, versus the romantic Mexican Cinderella story telenovela (Hernandez 2001), develop or emerge over time within those genre traditions. Television formats are now often distinguished as a parallel category which looks at forms of television that are packaged for licensing, transfer across cultures, and localized adaptation or implementation by regional, national or local networks. Speciﬁc formats are often imported and adopted. They can feed into genre development, grafted on to older traditions.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Global Television Formats : Circulating Culture, Producing Identity, 2012)
Livre : For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced in the US and UK markets and exported to foreign markets. This book explores how, thanks to recent technological innovation and globalization, television is now finally becoming truly global. Global Television Formats aims to revise the place of the global in television studies. The essays gathered here explore the diversity of global programming and approaches, and ask how to theorize contemporary
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Interpreting Cubanness, Americanness, and the Sitcom: WPBT-PBS’s ¿Qué pasa U.S.A.? (1975–1980) - Rivero, Yeidy M. (Global Television Formats: Understanding Television Across Borders, 2012)
I was about 10 or 11 years old when I, together with my parents, religiously tuned in weekly to the situation comedy ¿Qué pasa U.S.A.? While I do not recall the speciﬁc year the show aired in Puerto Rico, I do remember that it was broadcast on WIPR-Channel 6, the island’s public television station. Watching one of my favorite sitcoms on what I then considered the boring channel was rather odd. However, I never thought it strange that the Peñas, ¿Qué pasa U.S.A.? ’s working-class three-generation Cuban/Cuban-American family, resided in Miami or that some of the characters communicated bilingually in English and Spanish. For me, ¿Qué pasa U.S.A.? was a show that resembled other locally produced situation comedies broadcast on commercial television, with the difference that the Peña family were Cuban immigrants who, instead of residing in Puerto Rico (like some of my childhood friends), lived in Miami (like many of my friends’ relatives). Probably as a result of the principal characters’ cultural references and their accents in Spanish, I decoded ¿Qué pasa U.S.A.? as a Cuban sitcom. Fast-forward to 2004. I was invited to write a 500-word encyclopedia entry on ¿Qué pasa U.S.A.? Without having any information on the show at hand, I immediately accepted. This was an opportunity to revisit a program I loved. After conducting the research I realized the uniqueness of ¿Qué pasa U.S.A.? Sponsored by the U.S. Ofﬁce of Education Emergency School Assistance Act– Television Program (ESAA-TV), ¿Qué pasa U.S.A.? —considered the ﬁrst bilingual situation comedy broadcast on U.S. television— addressed the culturalgenerational misunderstandings and the socio-cultural adjustments endured by the Peñas, a 1960 Cuban exile family.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Cuba (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

NZ Idol: Nation Building Through Format Adaptation - De Bruin, Joost (Global Television Formats: Understanding Television Across Borders, 2012)
Three seasons of NZ Idol , the New Zealand adaptation of the global Idols format, were aired on public broadcaster TVNZ’s channel TV2 in 2004, 2005 and 2006. The ﬁnal episode of the ﬁrst season was the most-watched television programme in New Zealand in 2004, with 1.4 million people, a third of the New Zealand population, tuning in (South Paciﬁc Pictures, 2004). In terms of ratings NZ Idol has been one of the most successful locally made television programmes of the last decade. At ﬁrst glance, NZ Idol has also been very successful in representing ethnic and cultural diversity. In the auditions phase of the show young New Zealanders of 16 years plus from a range of backgrounds are featured, and in the subsequent phases the audience gets to know a selection of them intimately. The winners of all three seasons (Ben Lummis in season 1, Rosita Vai in season 2, and Matt Sounoa in season 3) have Paciﬁc Island roots, and as a result three young “brown” people were crowned “New Zealand Idols.” This is remarkable, since according to a previous study by Misha Kavka (2004: 231) non-white people have largely been absent from New Zealand reality TV programmes. A closer look suggests, however, that featuring contestants from different cultural backgrounds in NZ Idol generally serves a particular nation building agenda that New Zealand is heavily involved in as a postcolonial society, in which ethnic minorities are subjected to representations that favour the interests of dominant cultural groups. The aim of this nation building agenda is to establish a new and distinct sense of national identity which will set New Zealand apart from Britain, the former colonial power, and other English-speaking nations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Aotearoa/Nouvelle-Zélande (corpus analysé); Aotearoa/Nouvelle-Zélande (lieu de production du savoir); _Nettoyé

Global Television Formats in Africa: Localizing Idol - Nkosi Ndlela, Martin (Global Television Formats: Understanding Television Across Borders, 2012)
During the last decade, popular television formats have been replicated across the globe for local or regional consumption as program imports, adaptations, clones or imitations, raising questions on the possible ramiﬁcations of such cultural inﬂows. For Africa the international program ﬂow and the inﬂuence of Western media content has been a contentious issue for decades, underlying the cultural imperialism thesis of the 1970s and 1980s, and the centre– periphery paradigms which conceptualized the series of dependency relationships. In African media research concepts like cultural colonialism, media imperialism, neocolonialism, Americanization, homogenization, have been used to denote the unequal ﬂow and inﬂuence of Western media products in Africa. Within the framework of media globalization some scholars have even propounded a scenario of the emergency of a global culture mediated by the dominant Western media. The central issues in African media discussions have mainly revolved around the ﬂow of ﬁnished media programs and their perceived detriment to local cultures and identities. What is missing in the African research literature is the attention to television formats, a phenomenon described by Keane et al. (2002) as a vehicle for localization, since what is imported is not the content itself, but a recipe for creating a local version. Global reality format shows thus create a new picture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); Ghana (corpus analysé); Nigéria (corpus analysé); Norvège (lieu de production du savoir); _Nettoyé